MENENTUKAN PRIORITAS PILIHAN MAHASISWA DALAM MEMILIH KAMPUS MENGGUNAKAN ANALISIS CONJOINT - Maxsi Ary (Jurnal Informatika, 2015)
ABSTRACT - A private college is education marketers that need to identify students for educational products; educational products develop and implement a promotion to attract attention and give a strong response from prospective students. Advantages of private college to attract more students improved. The aim of this study is to analyze the preferences of students from the Department of Information Management AMIK Bandung BSI in choosing the campus. Research preferences in choosing college students conducted by applying conjoint analysis using SPSS 17.0. How that is done is to obtain a score of uses that can represent every aspect of campus services owned factor, so that on that score can be deduced about what attributes are most considered by the students in choosing a college. Results of the respondents preference highest-value is a factor field (14.92%), curriculum (13:21%), accreditation (12.75%), lecturer (12:13%), building (11.96%), library (11.87%), Distance (11.66%) and advertising (11:46%). Results of the aggregate utility level factors/attributes chosen by respondents, that the respondents liked the selection of educational services in the campus is having a field campus, open curriculum (the administration delivered in advance at the beginning of registration), the campus has been accredited, senior lecturer option, the size of ordinary buildings (less noticed), the library has a large collection of books, the distance between the house and near the campus, and advertising less attention. Keywords: Multivariate Statistics , Conjoint Analysis , Preference ABSTAKSI - Perguruan tinggi swasta merupakan pemasar pendidikan yang perlu mengidentifikasi calon mahasiswa terhadap produk pendidikan, mengembangkan produk pendidikan dan menerapkan promosi untuk menarik perhatian dan memberi tanggapan yang kuat dari calon mahasiswa. Keunggulan perguruan tinggi swasta untuk menarik minat mahasiswa lebih ditingkatkan. Tujuan dari penelitian ini adalah menganalisis preferensi mahasiswa Jurusan Manajemen Informatika AMIK BSI Bandung dalam memilih kampus. Penelitian preferensi mahasiswa dalam memilih kampus dilakukan dengan mengaplikasikan analisis conjoint menggunakan SPSS 17.0. Cara yang dilakukan adalah dengan memperoleh skor kegunaan yang dapat mewakili setiap aspek faktor jasa kampus yang dimiliki, sehingga dari skor tersebut dapat ditarik kesimpulan tentang atribut apa saja yang paling dipertimbangkan oleh mahasiswa dalam memilih kampus. Hasil preferensi responden yang bernilai paling tinggi adalah faktor Lapangan (14.92%), Kurikulum (13.21%), Akreditasi (12.75%), Dosen (12.13%), Gedung (11.96%), Perpustakaan (11.87%), Jarak (11.66%), dan Iklan (11.46%). Hasil utilitas agregat level faktor/atribut pilihan responden, bahwa responden menyukai jasa pendidikan dalam pemilihan kampus adalah kampus memiliki lapangan, kurikulum terbuka (pihak administasi menyampaikan terlebih dahulu diawal pendaftaran), kampus telah terakreditasi, pilihan dosen senior, ukuran gedung biasa saja (kurang diperhatikan), perpustakaan memiliki banyak koleksi buku, jarak antara rumah dan kampus dekat, dan iklan kurang diperhatikan. Kata Kunci: Statistik Multivariat, Analisis Conjoint, Preferensi